Dyskurs instytucjonalny i wiedza prawna w kształceniu studentów Lingwistyki w Komunikacji Specjalistycznej. Studium przypadku: Praktyczna Nauka Niemieckiego w Biznesie i Administracji - Kozłowska, Joanna (2022)
The MA programme, Linguistics in Specialized Communication, is intended as the continuation of Linguistics for Business BA-level studies. Contrary to L4B, the focus is put on linguistic preparation of active participation in the institutional discourse, both private and public sector. This paper argues that not only linguistic competences, but also basic knowledge of law should be required for students at MA studies in order to participate in the specialized communication.
Keywords: LSP; institutional discourse; specialized communication; linguistics in specialized communication